Intelligent robot arm using AVR microcontroller / Nuzaimah Hanifah - Hanifah, Nuzaimah (2007)
This project is a development of robot arm using ATMega8535 microcontroller. The robot arm capable to grasp, hold, lift and put any object from one place to another place. This low cost prototype of robot arm is designed to pick up an unused paper on the floor. The robot arm systems utilize a keypad and implementation of C language programming to control it movement. It is an open loop system with two degree of freedom (DOF) and two reliable axes which able to move up, down, right and left. It also consist of four design part includes the base, elbow, wrist and the gripper. Robotic arm that being programmed from AVR microcontroller chip is connected to three servo motor. The servo motor is acts as actuator which will move according to the angular position required